Biostratigraphy of Euphrates, Dhiban, and Jeribe formations in Ajil oil field, Salah Al-Deen Governorate, central Iraq - Alkhaykanee, Mustafa H.; Al-Dulaimi, Salam Ismeal (Iraqi Journal of Science, 2019)
The studied succession (Lower Miocene-Early Middle Miocene) In central Iraq is distinguished by a wide range of fossils, mostly benthic foraminifera, and other fossils including bivalves, gastropods, echinoids fragments, red algae and coral are also presented. Index fossils of benthic foraminifera have been used for the purpose of determining the age of the Euphrates and Jeribe formations, because of their young age, wide geographical distribution and abundance in the selected wells.The present study involves four selected wells of Ajil oil field and in terms of the biostratigraphy of the Euphrates, Dhiban, and Jeribe formations depending on benthic foraminifera and other associated fossils. Some of these fossils have a short vertical distribution, while others have long vertical distribution. There are two biozones determined. First, in Euphrates Formation "Ammonia beccarii-Miogypsina globulina" (Assemlage zone) Second in Jeribe Formation "Borelis melo curdica" (range zone). Dhiban Formation include only small pieces of distorted fossils and dominated by anhydrite, therefore it lacks the biostratigraphic zonation.